COLORS OF LOVE : WHEN ADULT WOMEN HAVE BACKSTREET RELATIONSHIP - Wahyu Rahardjo (Jurnal Psikologi, 2008)
For most women, age over 25 is the right moment to get married to fulfill one of her developmental task. Because of that, backstreet dating behavior usually done by person in order to keep maintenance the relationship before marriage. The aim of this study is to get comprehensive description about why an adult women fight to keep her backstreet dating behavior. This case study has a 30 years old women who still running in backstreet dating behavior as a participant. The result shows that participant does this backstreet behavior because of reasons such as the differences in religion, age, educational and job background. She maintenances the relationship because (1) that is the first time she had a boyfriend, (2) she has storage-fragma type of love, so she really commit to the relationship, and (3) the caring of her boyfriend.Key words: backstreet dating behavior, colors of love